Local Features of English Pronunciation: To Embrace or Ignore in the ELT Classroom? - Pillai, Stefanie (Journal of English Language, Literature, and Teaching (J-ELLiT), 2017)
English around the world is spoken in a multitude of accents, and this includes spoken Standard English. Yet, in some ELT contexts, there is still a fixation with using a native model of pronunciation. Such targets do not tend to take into consideration local English pronunciation features. This leads to either the teaching of English pronunciation being largely ignored in the classroom, or in teachers attempting to teach features that students are unlikely to hear in the local contexts. In this paper, I will explore some of the features of pronunciation in Malaysian English, and show how these do not align with the curriculum specifications for pronunciation. I will then discuss how teachers in other ELT contexts can deal with these issues in the classroom.